Evaluation of Annual Statice (Limonium sinuatum L.) Cultivars - S K Nataraj; P M Gangadharappa; B S Reddy; K B Naik; S J Prashanth; D P Prakash (Journal of Horticultural Sciences, 2009)
A field study was conducted during rabi season of 2003-2004 to evaluate the potential of statice cultivars as cut flower crop in the field of Department of Floriculture and Landscape Gardening, K.R.C. College of Horticulture, Arabhavi. The experiment was laid out as a Randomised Block Design with four replications. The panicles of each variety were harvested when calycys of individual flower have mostly opened and showing colour. The cultivar Turbo White recorded maximum plant height (21.78 cm), panicle length (80.94 cm), stem diameter (0.61 cm), no. of leaves (186.60), maximum fresh weight of panicles (530.09 g/plant), plant spread 62.15 cm2 and remained superior over others. The results are in agreement with the findings of Angadi (2000) in China aster. Maximum panicle production per plant (25.64) was recorded in cv. Turbo White, which was on par with the cultivar Turbo Carmine (22.54). The results were in line with the findings of Kumar et al. (1998) in annual statice Turbo White. The cultivar Turbo White was good in quality parameters by recording maximum panicle length, girth and number of branches per panicle. It was also vigorous in vegetative growth. Therefore, the cultivar could produce better quality panicles and found to be suitable for semi arid regions.